Children Blunt Abdominal Trauma at Khartoum Teaching Hospital (Global Journal of Medical Research, 2014)
Background : Paediatric trauma is expected by the WHO to be the number one disease globally in 2020. Although the abdomen is the third most commonly injured anatomic region in children following the head and extremities, blunt abdominal trauma is the most common cause of initially unrecognized fatal injuries. Objectives : To study mechanisms of injury, presentation, management and outcome of paediatrcis blunt abdominal trauma in KTH. Patients and methods: This is a prospective observational descriptive study involving children aged less than 15 years presenting to KTH with blunt abdominal trauma. The study conducted in the period from March 2012 to August 2013. Results: There were 50 patients. The mean age was 7 years. Male to female ratio was 2:1. There was a wide spectrum of causative trauma. The most frequent cause was RTA 40% .Solid organ injuries were (70%), intestinal injuries (12%), diaphragmatic hernia (2%), abdominal wall haematoma (2%), NOM for solid organs injuries was successful in 94%. There were 3 deaths (6%). Two of them associated with head injuries and one was delayed intestinal perforation. Conclusion: The majority of children with blunt abdominal solid organs injuries can be treated successfully without surgery, associated head injuries and delayed intestinal perforation were main causes of mortality.
Keywords: abdominal trauma; abdominal injury; children; paediatrics; blunt